Lisfranc fracture-dislocation with associated ipsilateral ankle fracture - García Martínez, María Cristina; González Ustés, Javier; Marrero Riverón, Luis Oscar (Revista Cubana de Ortopedia y Traumatología, 2023)
Lisfranc fracture dislocation is a rare entity which often occurs in a high energy context. Meanwhile, bimalleolar or trimalleolar fractures are much more common, and can happen in both low and high energy. However, both lesions rarely occur together. As far as we know, it has only been described twice in the literature. We present a case series of two cases consisting of Lisfranc fracture-dislocation plus associated bimalleolar or trimalleolar fracture, which were correctly diagnosed and furthermore treated in our center within a 3-year follow up.